2019 13th International Symposium on Medical Information and Communication Technology (ISMICT) 2019
DOI: 10.1109/ismict.2019.8744003
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity Metrics for Enhanced Protection of Healthcare IT Systems

Abstract: Cybersecurity incidents are on the rise in the healthcare sector and it is becoming a growing concern for the senior executives. The attack surface is expanding due to the large number of connected medical devices and the proliferation of portable devices such as smart phones, tablets and USB devices. In this paper, we will discuss some of the security challenges facing this sector and propose a set of cybersecurity metrics that could be used to enhance the protection of the IT systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 54 publications
1
10
0
Order By: Relevance
“…Cyberattacks can cause serious consequences such as information dissemination, falsification, service failure, server congestion, and changes in medical image resolution. In this way, the bow-tie methodology contributes to improve cybersecurity practices in telemedicine, which is affected by several factors including training rate, security policies, security certification, risk management capacity, IT governance, and management security costs [ 60 ]. The bow-tie model for cybersecurity in telemedicine is based on the related literature (which are shown in Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cyberattacks can cause serious consequences such as information dissemination, falsification, service failure, server congestion, and changes in medical image resolution. In this way, the bow-tie methodology contributes to improve cybersecurity practices in telemedicine, which is affected by several factors including training rate, security policies, security certification, risk management capacity, IT governance, and management security costs [ 60 ]. The bow-tie model for cybersecurity in telemedicine is based on the related literature (which are shown in Table 2 and Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a general way, the bow-tie approach was created for security management and used mainly to identify threats, analyze barriers, and assess operational risks. In this sense, bow-tie analysis, which is a combination of FTA and ETA, is very popular because it incorporates both the causes and consequences of the incident scenario and can be used to assess all kinds of risks such as the ones regarding gas and oil pipelines [ 56 , 57 ], occupational risks [ 58 ], and industrial risks [ 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the threats that healthcare faces are attacks on their medical devices, services they provide and their infrastructure, that could affect safety and well-being of their patients, indirectly harming them and possibly causing more health problems, and in worst case scenario, even death [67]. Reports have shown that healthcare infrastructure is among the most frequently targeted industries for cyber-attacks.…”
Section: Healthcarementioning
confidence: 99%
“…It is emphasized that cybersecurity should not be analyzed only as a compliance practice given the occurrence of specific events causing additional costs [7,8], but should be designed in a structured and contingent way to consider all systems from the conception of telemedicine systems and services to be offered [9,10]. Deficiencies in the ICT infrastructure of these services contribute significantly to the increase of harmful attacks on health organizations that also adopt the strategy of promoting their services remotely [11].…”
Section: Introductionmentioning
confidence: 99%